Exploration Of Instagram Usage As A Learning Media For Arabic Language (Content Analysis on Instagram Account @takallam.arabiyyah): - - Khofiyya, Nida An; Nurmala, Mia; Tatang, Tatang (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The widespread use of social media in the current 4.0 era signifies that it has become a necessity for society, with one notable platform being the Instagram application. Instagram serves as a platform for users to share their moments through photos and videos. This research aims to demonstrate to Instagram users that the platform offers additional benefits, particularly as a medium for learning Arabic more easily and efficiently. The method employed in this research is qualitative. The researcher assumes a pivotal role as the primary data collection tool, comprehending the context and analyzing information acquired from the Instagram account @takallam.arabiyyah. The primary data collection technique utilized is content analysis, involving the examination of verbal and visual data from social media. This article will delve into the utilization of the Instagram account @takallam.arabiyyah as a medium for learning Arabic, as well as explore the advantages and disadvantages of Instagram as a platform for Arabic language learning.